Analysis of technological operation – flat sheet metal forming of car body panels - Trunova, I.; Belan, A.; Bondarenko, D.; Трунова, І. С.; Белан, А. Д.; Бондаренко, Д. О.; Трунова, И. С.; Бондаренко, Д. А. (Харківський національний автомобільно-дорожній університет, 2014)
The group operations of magnetic-pulse metal working were considered. The analysis of technological operations carried out according to the scheme flat sheet stamping has been conducted.
Аналіз технологічної операції – плоске листове штампування кузовних панелей автомобілів
Анализ технологической операции – плоская листовая штамповка кузовных панелей автомобилей
Keywords: magnetic-pulse metal working; magnetic-pulse forming; inductor; car body panels; магнітно-імпульсна обробка металів; магнітно-імпульсне штампування; індуктор; кузовна панель; магнитно-импульсная обработка металлов; магнитно-импульсная штамповка; индуктор; кузовная панель; 621.318